Heavy metal concentrations in wild fishes captured from the South China Sea and associated health risks. Issue 1 (15th July 2015) - Gu, Yang-Guang; Lin, Qin; Wang, Xue-Hui; Du, Fei-Yan; Yu, Zi-Ling; Huang, Hong-Hui
Graphical abstract: Highlights: Trace metals in wild marine fish from the South China Sea were investigated. Metal concentrations descended in the following order: Fe > Zn > Cr > Cu > Mn > Ni > Cd > Pb. The Fe and Mn may be potential risk to human. No obvious health risk from the intake of trace elements through fish consumption. Abstract: Heavy metal concentrations were measured in 29 marine wild fish species from the South China Sea. Concentrations (wet weight) were 0.51–115.81 ng/g (Cd), 0.54–27.31 ng/g (Pb), 0.02–1.26 μg/g (Cr), 8.32–57.48 ng/g (Ni), 0.12–1.13 μg/g (Cu), 2.34–6.88 μg/g (Zn), 2.51–22.99 μg/g (Fe), and 0.04–0.81 μg/g (Mn), respectively. Iron concentrations in all and Mn in some fish species were higher than the acceptable daily upper limit, suggesting human consumption of these wild fish species may pose a health risk. Human health risk assessment, however, indicated no significant adverse health effects with consumption.